Risk factors for advanced duodenal and ampullary adenomatosis in familial adenomatous polyposis: a prospective, single-center study - Sulbaran, M.; Campos, F. G.; Ribeiro, U., Jr.; Kishi, H. S.; Sakai, P.; de Moura, E. G. H.; Bustamante-López, L.; Tomitão, M.; Nahas, S. C.; Cecconello, I.; Safatle-Ribeiro, A. V. (Endoscopy International Open, 2018)
Background and study aims To determine the clinical features associated with advanced duodenal and ampullary adenomas in familial adenomatous polyposis. Secondarily, we describe the prevalence and clinical significance of jejunal polyposis.Patients and methods This is a single center, prospective study of 62 patients with familial adenomatous polyposis. Duodenal polyposis was classified according to Spigelman and ampullary adenomas were identified. Patients with Spigelman III and IV duodenal polyposis underwent balloon assisted enteroscopy. Predefined groups according to Spigelman and presence or not of ampullary adenomas were related to the clinical variables: gender, age, family history of familial adenomatous polyposis, type of colorectal surgery, and type of colorectal polyposis.Results Advanced duodenal polyposis was present in 13 patients (21 %; 9 male) at a mean age of 37.61 ± 13.9 years. There was a statistically significant association between family history of the disease and groups according to Spigelman (P = 0.03). Seven unrelated patients (6 male) presented ampullary adenomas at a mean age of 36.14 ± 14.2 years. The association between ampullary adenomas and extraintestinal manifestations was statistically significant in multivariate analysis (P = 0.009). Five endoscopic types of non-ampullary adenoma were identified, showing that lesions larger than 10 mm or with a central depression presented foci of high grade dysplasia. Among 28 patients in 12 different families, a similar Spigelman score was identified; 10/12 patients (83.3 %) who underwent enteroscopy presented small tubular adenomas with low grade dysplasia in the proximal jejunum.Conclusions Advanced duodenal polyposis phenotype may be predictable from disease severity in a first-degree relative. Ampullary adenomas were independently associated with the presence of extraintestinal manifestations.Study registration: NCT02656134